Telemedicine awareness and the preferred digital healthcare tools: A community-based cross-sectional study from rural Karnataka, India - Parvathi Malladra Parameshwarappa; Jeby Jose Olickal (Wolters Kluwer Medknow Publications, 2023)
Background: The Indian government launched national teleconsultation services (eSanjeevani OPD) to provide safe doctor-to-patient consultations. This study aimed to determine the awareness and willingness to seek services from eSanjeevani OPDs. Material and Methods: This is a cross-sectional descriptive study conducted in Nandigudi village, Karnataka. The total sample size was 273, and participants were recruited using a systematic sampling technique. Results: The prevalence of awareness about teleconsultations was 2.2% (n = 6, 95% CI: 0.8-4.7%). None of the participants utilized eSanjeevani services in the last year. Approximately 56.0% (n = 153, 95% CI: 49.9-62.0%) were willing to use eSanjeevani OPD. "Not being familiar" (n = 99, 82.5%) with eSanjeevani OPD was the major reason for unwillingness to use teleconsultation, and 73.8% (n = 113) preferred video calls as the mode of communication. Conclusion: The majority of the participants were not aware of and were unwilling to use eSanjeevani OPD. Therefore, healthcare professionals should focus more on creating awareness of teleconsultations.